2016
DOI: 10.1080/15374416.2016.1253017
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ and Best Friend’s Depressive Symptoms and Conflict Management: Intraindividual and Interpersonal Processes Over Time

Abstract: This 6-year longitudinal study examined the relation between 3 conflict management styles (i.e., problem solving, conflict engagement, and compliance) and depressive symptoms in adolescent-best friend relationships. Participants were 479 Dutch adolescents and their best friend who reported annually on depressive symptoms and conflict management styles toward each other. Bidirectional effects between conflict management styles and depressive symptoms were studied both within adolescents (intraindividual) and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Although not of main interest to our study and not officially tested, we also found that friends seem to become more alike in their level of depressive symptoms over time (as indicated by increasing ICCs). This finding is in concurrence with other studies (Boersma-van Dam et al, 2019;Schwartz-Mette & Smith, 2018;Van Zalk et al, 2010) and emphasizes that early monitoring of friends with elevated depression symptoms is warranted.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although not of main interest to our study and not officially tested, we also found that friends seem to become more alike in their level of depressive symptoms over time (as indicated by increasing ICCs). This finding is in concurrence with other studies (Boersma-van Dam et al, 2019;Schwartz-Mette & Smith, 2018;Van Zalk et al, 2010) and emphasizes that early monitoring of friends with elevated depression symptoms is warranted.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, in our study, no associations of support and subsequent depressive symptoms were found at the individual level. Although previous studies did not differentiate between dyadic and individual effects, some studies have suggested that dyadic processes such as depression contagion via peer influence or selection effects might play a role in the development of depressive symptoms within adolescent friendships (Boersma-van Dam et al, 2019;Brechwald & Prinstein, 2011;Giletta et al, 2011;Van Zalk et al, 2010). The present study confirmed this suggestion and emphasizes that part of the supportdepression association may be due to either selection or within dyad processes, or both, that may make friendship dyads similar in the appreciation of support in their experienced mental state (Mankowski & Wyer, 1996;Van Zalk et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations